The role of antibodies to Plasmodium falciparum-infected-erythrocyte surface antigens in naturally acquired immunity to malaria. - Bull, P; Marsh, K (2002)
Plasmodium falciparum, the most virulent species of human malaria parasite, causes 1-3 million deaths per year. Because this parasite is susceptible to naturally acquired host immunity the main burden of diseases falls on young children. The mechanism of this immunity is still unclear. However, the parasite makes a considerable investment in the insertion of highly polymorphic antigens (parasite-infected-erythrocyte surface antigens, PIESA) on the infected erythrocyte surface, and these antigens are potentially important immune targets.